2014
DOI: 10.1002/art.38374
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of the Relationship Between External Knee Adduction Moments and Medial Joint Contact Forces Across Subjects and Activities

Abstract: ObjectiveThe external knee adduction moment (EAM) is often considered a surrogate measure of the distribution of loads across the tibiofemoral joint during walking. This study was undertaken to quantify the relationship between the EAM and directly measured medial tibiofemoral contact forces (Fmed) in a sample of subjects across a spectrum of activities.MethodsThe EAM for 9 patients who underwent total knee replacement was calculated using inverse dynamics analysis, while telemetric implants provided Fmed for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
60
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 82 publications
(65 citation statements)
references
References 51 publications
3
60
0
Order By: Relevance
“…The first peak of the EAM during the stance phase was [16,17]. One of the reasons seems to be that antagonistic muscle activities, which raise the joint contact force, are not reflected in gait analysis data.…”
Section: Introduction (Word Count Main Text: 3759)mentioning
confidence: 79%
“…The first peak of the EAM during the stance phase was [16,17]. One of the reasons seems to be that antagonistic muscle activities, which raise the joint contact force, are not reflected in gait analysis data.…”
Section: Introduction (Word Count Main Text: 3759)mentioning
confidence: 79%
“…The study also identified strategies for proper tuning of this parameter which we used in this study [28]. Although previous investigations have found that the medial-lateral force ratio is correlated with the external knee adduction moment [23,29], it is uncertain as to whether this relationship holds true for all activities and whether it may be influenced by patient characteristics such as knee alignment [30,31]. Specifically, for chair sitting and rising the medial-lateral force ratio of 50%, indicating equal force transfer between the medial and lateral sides of the tibial plateau, was necessary to obtain forces with the computational model.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, for chair sitting and rising the medial-lateral force ratio of 50%, indicating equal force transfer between the medial and lateral sides of the tibial plateau, was necessary to obtain forces with the computational model. A previous study of instrument prostheses, although with a more constrained prosthesis design, also found the percentage of force transmitted medially through the knee to be lower for chair activities than stair and walking activities [32,31]. …”
Section: Discussionmentioning
confidence: 99%
“…1, right) sagittal plane frontal plane highlights a cause for a potential training-induced damage. High external knee adduction moments reflect high compressive forces acting on the medial knee compartment (Kutzner et al (2013)) and are supposed to foster osteoarthritis (OA) development and progression, when occurring during locomotion (Reeves and Bowling (2011), Andriacchi et al (2004), Trepczynski et al (2014)). Thus, training in the leg press with OA patients and elderly people should focus to reduce knee adduction moments.…”
Section: Introductionmentioning
confidence: 99%